Adverse pregnancy outcomes following a job loss in the UK - Alessandro Di Nallo; Selin Köksal (University of Essex, Institute for Social and Economic Research (ISER), 2022)
Research has documented that economic downturns increase the risk of pregnancy loss. However, previous work on has not addressed the influence of in utero exposure to job loss with high-quality individual data. We draw on 'Understanding Society' (UKHLS, sweeps 1-11, 2009-2020), which contains a sample of 7,698 pregnancies. The dependent variable identifies a non-live birth, namely a miscarriage or a stillbirth. We examine the couples who were exposed to an involuntary job loss and those who were not. Baseline models controlling for women's socio-demographic background and prior experience of miscarriage indicate an increased risk of pregnancy loss when exposed to in utero job loss [odds ratio (OR) = 2.16, 95% CI: 1.42, 3.29]. When we account for all current socio-economic characteristics, the association remains statistically significant [odds ratio (OR) =1.96, 95% CI: 1.29, 2.98]. The findings support the inference that the in utero exposure to an involuntary job loss increases the risk of pregnancy disruption.
Keywords: 330; pregnancy loss; stillbirth; miscarriage; job loss; UK